2019
DOI: 10.1093/annonc/mdz288
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes to first-line pembrolizumab in patients with non-small-cell lung cancer and very high PD-L1 expression

Abstract: Background: In non-small-cell lung cancers with programmed death-ligand 1 (PD-L1) expression on 50% of tumor cells, firstline treatment with the PD-1 inhibitor pembrolizumab improves survival compared with platinum-doublet chemotherapy. Whether higher PD-L1 levels within the expression range of 50%-100% predict for even greater benefit to pembrolizumab is currently unknown.Patients and methods: In this multicenter retrospective analysis, we analyzed the impact of PD-L1 expression levels on the overall response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
185
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(206 citation statements)
references
References 23 publications
20
185
0
1
Order By: Relevance
“…Finally, our study has several limitations including notably the lack of biological data including PD-L1 status [24][25][26] . We failed to collect this crucial data as biomarker analysis has not been universalized in clinical practice until very recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our study has several limitations including notably the lack of biological data including PD-L1 status [24][25][26] . We failed to collect this crucial data as biomarker analysis has not been universalized in clinical practice until very recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Immunotherapy has been demonstrated particularly successful in NSCLC treatment and is being adopted as a rst-line treatment option worldwide [13,22,42]. Nevertheless, only a small portion of the unselected patients can bene t from immunotherapy [25,43].…”
Section: Discussionmentioning
confidence: 99%
“…Four ICIs that targeting PD-1 or PD-L1 have been approved by the U.S. Food and Drug Administration (FDA) for treatment in patients with non-small cell lung cancer (NSCLC) [12]. Furthermore, a large amount of clinical research had demonstrated that immunotherapy alone or in combination with chemotherapy could be used for rst-line treatment of patients with metastatic lung cancer [13][14][15][16]. It was reported that patients with higher PD-L1 expression had better outcomes compared to patients with lower or no PD-L1 expression using the anti-PD-L1 antibody clone 22C3 [17].…”
Section: Introductionmentioning
confidence: 99%
“…Immune checkpoint inhibitors such as antibodies against PD-L1 and PD-1 have been introduced into clinical practice for a number of cancers [117,118]. In HCC, double-blind randomized clinical trials studies have shown that immune checkpoint inhibitor therapy can provide favorable responses in patients with advanced HCC [119].…”
Section: Exosomal Mirnas' Future Implications For Immunotherapy In Hccmentioning
confidence: 99%